Design of a Substrate-Integrated Fabry-Pérot Cavity Antenna for K-Band Applications - Truong Khang Nguyen; Ikmo Park (International Journal of Antennas and Propagation)
This paper presents the design of a planar, low-profile, high-gain, substrate-integrated Fabry-Pérot cavity antenna for K-band applications. The antenna consists of a frequency selective surface (FSS) and a planar feeding structure, which are both lithographically patterned on a high-permittivity substrate. The FSS is made of a circular hole array that acts as a partially reflecting mirror. The planar feeding structure is a wideband leaky-wave slit dipole fed by a coplanar waveguide whose ground plane acts as a perfect reflective mirror. The measured results show that the proposed antenna has an impedance bandwidth of more than 8% (VSWR ≤ 2), a maximum gain of 13.1 dBi, and a 3 dB gain bandwidth of approximately 1.3% at a resonance frequency of around 21.6 GHz. The proposed antenna features low-profile, easy integration into circuit boards, mechanical robustness, and excellent cost-effective mass production suitability.